2018
DOI: 10.1111/sms.13215
|View full text |Cite
|
Sign up to set email alerts
|

Validity and generalizability of findings of randomized controlled trials on arthroscopic partial meniscectomy of the knee

Abstract: The validity and generalizability of evidence from trials on arthroscopic partial meniscectomy (APM) for a ruptured meniscus of the knee has been debated in scientific journals. The aim of this paper was to assess the validity and generalizability of evidence for trials on effectiveness of APM by a novel Benchmarking method; to compare this assessment with established assessment methods; and to make an overall assessment of the current evidence on validity and generalizability of findings. Literature search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…43,68,73 Substantial evidence is available demonstrating no difference in clinical outcomes for APM versus conservative management for degenerative meniscal tears 1,70,77,78,106,132 ; however, the available evidence may be biased and of low quality. 58,87 Clinical outcomes tended to improve after APM and reoperation rates were low, although knee osteoarthritis is likely to develop after APM. 13,102,104 Meniscal repairs have been associated with good clinical outcomes overall, 45,81,143 and for isolated meniscal repairs there has been no difference in clinical outcomes between all-inside versus inside-out repairs.…”
Section: Discussionmentioning
confidence: 99%
“…43,68,73 Substantial evidence is available demonstrating no difference in clinical outcomes for APM versus conservative management for degenerative meniscal tears 1,70,77,78,106,132 ; however, the available evidence may be biased and of low quality. 58,87 Clinical outcomes tended to improve after APM and reoperation rates were low, although knee osteoarthritis is likely to develop after APM. 13,102,104 Meniscal repairs have been associated with good clinical outcomes overall, 45,81,143 and for isolated meniscal repairs there has been no difference in clinical outcomes between all-inside versus inside-out repairs.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was the only RCT with comprehensive recruitment from a catchment area, which provided adequate representation of the population 33 and demonstrated a statistically and clinically significant positive effect of knee arthroscopic surgery with an exercise program after 1 year compared with an exercise program alone. 15 The objectives of the present study were to (1) evaluate whether knee arthroscopic surgery combined with an exercise program provided an additional 5-year benefit compared with an exercise program alone in middle-aged patients with meniscal symptoms, (2) determine whether baseline mechanical symptoms affected the outcome, and (3) compare radiographic changes between treatment groups.…”
mentioning
confidence: 86%
“…5,52,54 Nevertheless, the role of arthroscopic surgery in the treatment of degenerative meniscal tears remains controversial. 2,30,33 A recent review concluded that these patients could benefit from arthroscopic meniscectomy but that nonsurgical treatment should be considered first. 29 Mechanical symptoms were previously considered an indication for surgery; however, recent data have contradicted this tenet.…”
mentioning
confidence: 99%
“…Baseline comparability (the aim of randomization), description of adherence to interventions (a causal factor), and the validity of the outcome (effect) was assessed in 7%, 7% and 5% of the SRs, respectively. As these vital validity factors of an RCT are lacking, the appraisal of internal validity of individual RCTs is seriously impaired (24,25).…”
Section: Discussionmentioning
confidence: 99%